The Tests of English Grammar Made by The Lecturers of English Department of Universitas Negeri Makassar - Jabu, Baso (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2022)
This study aims at describing the profile of the teacher-made tests of English grammar at State University of Makassar. The result of analysis revealed that the instructional objectives and the materials were not fully represented by the tests provided by the lecturers; the teaching and learning activities were suitable with the prescribed strategies in the syllabus; the learning activities did not match the test in terms of test activity; the purpose of the tests was achievement and the test type was objective in different test techniques: correcting, error identification, completion, transformation, and true-false, with single marking system; the cognitive domains were applying and understanding; and the teacher-made tests were not quite valid, not highly reliable, with some items of proper level of difficulty and discrimination index.Keywords: profile, teacher-made grammar test, test criteria